The Multi‐Decadal Response to Net Zero CO2 Emissions and Implications for Emissions Policy. Issue 23 (1st December 2022) - Jenkins, Stuart; Sanderson, Ben; Peters, Glen; Frölicher, Thomas L.; Friedlingstein, Pierre; Allen, Myles
Abstract: How confident are we that CO2 emissions must reach net zero or below to halt CO2 ‐induced warming? The IPCC's sixth assessment report concluded that "limiting human‐induced global warming to a specific level requires … reaching at least net zero CO2 emissions." This is much stronger language than the special report on the global warming of 1.5°C, which concluded that reaching net zero CO2 emissions would be sufficient. Here we show that "approximately net zero" is better supported than "at least net zero." We estimate the rate of adjustment to zero emissions (RAZE) parameter (−0.24 to +0.17%/yr), defined as the fractional change in CO2 ‐induced warming after CO2 emissions cease. The RAZE determines the CO2 emissions compatible with halting warming over multiple decades: in 1.5°C‐consistent scenarios, CO2 emissions consistent with halting anthropogenic warming are +2.2 GtCO2 /yr (5–95th percentile range spans −7.3 to +6.2 GtCO2 /yr), similar to the expected emissions from unmodelled Earth system feedbacks. Plain Language Summary: How confident are we that CO2 emissions will need to reach net zero (where human‐made CO2 emissions into the atmosphere are approximately balanced with CO2 removals through carbon capture and storage, nature‐based solutions, etc.) or below to halt human‐induced warming? Here we show that "approximately net zero" is the best‐estimate requirement to stabilize warming. To do this we show that the behavior of the climate system's temperature response following net zero can be defined using a new parameter (the rate of adjustment to zero emissions, RAZE), which spans −0.24 to +0.17%/yr. The RAZE determines the ongoing rate of CO2 emissions or removals compatible with halting warming. In scenarios which reach approximately 1.5°C warming, CO2 emissions consistent with halting human‐made warming over multi‐decadal timescales span −7.3 to +6.2 GtCO2 /yr with a best‐estimate of +2.2 GtCO2 /yr. Planning for net negative global CO2 emissions remains important, given the chance of global temperatures overshooting 1.5°C, along with research to better understand the emissions consistent with warming stabilization. Key Points: The conditions for stabilization of global temperature at any level depend on the multi‐century carbon and thermal cycle response This is described by the rate of adjustment to zero emissions parameter, spanning −0.24 to +0.17%/yr (−0.036 to 0.025°C/decade at 1.5°C) In 1.5°C scenarios, CO2 emissions consistent with halting anthropogenic warming over multi‐decadal timescales span −7.3 to +6.2 GtCO2 /yr